Parameter optimization for proton density fat fraction quantification in skeletal muscle tissue at 7 T - Tkotz, Katharina; Zeiger, Paula; Hanspach, Jannis; Mathy, Claudius; Laun, Frederik Bernd; Uder, Michael; Nagel, Armin Michael; Gast, Lena (Magnetic Resonance Materials in Physics Biology and Medicine, 2024)
Objective: To establish an image acquisition and post-processing workflow for the determination of the proton density fat fraction (PDFF) in calf muscle tissue at 7 T. Materials and methods: Echo times (TEs) of the applied vendor-provided multi-echo gradient echo sequence were optimized based on simulations of the effective number of signal averages (NSA*). The resulting parameters were validated by measurements in phantom and in healthy calf muscle tissue (n = 12). Additionally, methods to reduce phase errors arising at 7 T were evaluated. Finally, PDFF values measured at 7 T in calf muscle tissue of healthy subjects (n = 9) and patients with fatty replacement of muscle tissue (n = 3) were compared to 3 T results. Results: Simulations, phantom and in vivo measurements showed the importance of using optimized TEs for the fat–water separation at 7 T. Fat–water swaps could be mitigated using a phase demodulation with an additional B0 map, or by shifting the TEs to longer values. Muscular PDFF values measured at 7 T were comparable to measurements at 3 T in both healthy subjects and patients with increased fatty replacement. Conclusion: PDFF determination in calf muscle tissue is feasible at 7 T using a chemical shift-based approach with optimized acquisition and post-processing parameters.
CRIS-Team Scopus Importer:2024-08-16
Keywords: 7 Tesla; Dixon MRI; Fat–water separation (FWS); Proton density fat fraction (PDFF); Skeletal muscle tissue